Migración de medios impresos hacia el ecosistema digital, en la ciudad de Machala - Andrade Carrión, Walter Cesar; Escobar Moncada, Joyce Thalia (Machala, 2021)
The theme of this research project is 'Migration of print media towards the Digital Ecosystem, in the city of Machala' and focuses mainly on defining the migration process, used by print media, to find a viable means that allows them to adapt and establish themselves as digital media. Its importance lies in promoting the dissemination of the migratory processes of adaptability that are carried out in the printed media, transferring the production of informative and entertainment content to digital platforms without losing its identity. These results were developed and verified with the purpose of demonstrating the coherence and discrepancy between different ways of evaluating print media, since these data obtained allow us to examine the difference in the migratory process towards the digital ecosystem that each one of them executed in order to adapt in a positive way. The first chapter called 'Approach to the research problem', consists of the formulation of the problem, objectives and questions of the study topic, which relates to the origin of the problem with the identification of the established variables, it also contains the justification and feasibility of the research that resolve the questions and objectives of the issue raised. Chapter II consists of the "theoretical and conceptual framework", where the antecedents, theoretical bases and the definition of basic terms or conceptualization are identified, managing to publicize the elementary pillars that justify this investigative work. In chapter III, called “methodological process”, he proposes that the research carried out from the critical point of view, of qualitative particularity, the research mode is documentary and bibliographic, which will allow the structuring in the study models that are generated based on the content analysis studied in the three print media. In this chapter, the measuring instrument was the interview, which was applied to 35 specialized people, including teachers and journalists who are experts in the area of ​​journalism for both print and digital media, this was carried out through various digital platforms which allowed great interaction and data exchange, allowing the gathering of information of great help for this analysis process, becoming the most valuable sources for this investigative work. To conclude, in chapter IV the results of the arduous investigation used are evidenced, managing to find outstanding information for the formulation of conclusions, the data obtained from the interviews were optimal, in order to be able to announce the effect that the multiple communication media had. at the time of applying the migration process to the digital ecosystem, emphasizing the three print media that the city of Machala has. It was possible to find outstanding information for the elaboration of conclusions and recommendations for both print and digital media, their characteristics, advantages, disadvantages and needs with respect to the adaptation of the current digital ecosystem, it was also sought to know the deficiencies that these media possess that were perceived by the interviewees, who provided very significant information, managing to reach timely suggestions to improve these processes.
El presente proyecto de investigación tiene como tema ‘Migración de medios impresos hacia el Ecosistema Digital, en la ciudad de Machala’ e incide principalmente en definir el proceso migratorio, que utilizan los medios de comunicación impresos, para encontrar un medio viable que les permita la adaptación y establecerse como medios digitales. Su importancia radica en fomentar la difusión de los procesos migratorios de adaptabilidad que se ejecutan en los medios de comunicación impresos, trasladando la elaboración de contenido informativo y de entretenimiento a las plataformas digitales sin perder su identidad. Estos resultados fueron desarrollados y verificados con el propósito de evidenciar la coherencia y discrepancia entre distintas maneras de valorar los medios impresos, puesto que estos datos obtenidos nos permiten examinar la diferencia del proceso migratorio hacia el ecosistema digital que ejecutaron cada uno de ellos para lograr adaptarse de una forma positiva. El primer capítulo denominado ‘Planteamiento del problema de investigación’, consta con la formulación del problema, objetivos y preguntas del tema de estudio, que hace relación al origen del problema con la identificación de las variables establecidas, además contiene la justificación y factibilidad de la investigación que resuelven las interrogantes y objetivos del tema planteado. El capítulo II consta con el “marco teórico y conceptual”, en donde se identifican los antecedentes, bases teóricas y la definición de términos básicos o conceptualización, logrando dar a conocer los pilares elementales que justifican este trabajo investigativo. En el capítulo III, denominado “proceso metodológico”, propone que la investigación que se efectúa desde el punto de vista crítico, de particularidad cualitativo, el modo de investigación es documental y bibliográfica, que posibilitará a la estructuración en los modelos de estudio que se generen en base al análisis de contenidos estudiados en los tres medios impresos de comunicación. En este capítulo el instrumento de medición fue la entrevista, la cual se aplicó a 35 personas especializadas entre ellos docentes y periodistas expertos en el área del periodismo tanto para medios impresos y digitales, esta fue ejecutada mediante diversas plataformas digitales las cuales permitieron una gran interacción e intercambio de datos, permitiendo recopilar información de gran ayuda para este proceso de análisis, convirtiéndose en las fuentes más valiosas para este trabajo investigativo. Para finalizar, en el capítulo IV se evidencian los resultados de la ardua investigación empleada, logrando encontrar información sobresaliente para la formulación de conclusiones, los datos que arrojaron las entrevistas fueron óptimos, para poder así anunciar sobre el efecto que tuvieron los múltiples medios de comunicación al momento de aplicar el proceso migratorio hacia el ecosistema digital, haciendo énfasis en los tres medios impresos que posee la ciudad de Machala. Se logró encontrar información destacada para la elaboración de conclusiones y recomendaciones para los medios de comunicación tanto impresos como digitales, sus características, ventajas, desventajas y necesidades con respecto a la adaptación del ecosistema digital actual, también se buscó conocer las deficiencias que poseen estos medios que fueron percibidos por los entrevistados, los cuales proporcionaron información muy significativa, logrando alcanzar sugerencias oportunas para poder mejorar estos procesos.
Keywords: ECOSISTEMA; DIGITAL; MEDIO IMPRESO; MEDIO DIGITAL